(untitled) - Lislaine Bomm; Marcela Duarte Villela Benez; Juan Manuel Piñeiro Maceira; Isabel Cristina Brasil Succi; Maria de Fatima Guimarães Scotelaro (Anais Brasileiros de Dermatologia, 2013)
It may be clinically difficult to differentiate early-stage melanoma from benign tumors, specially pigmented seborrheic keratosis. Dermoscopy can help; however, the findings are not always conclusive. Therefore, histopathology may be necessary for a correct diagnosis. We describe a melanocytic lesion with dubious clinic and dermoscopic findings. An incisional biopsy of a suspicious area, guided by dermoscopy, was performed to clarify the findings. A diferença clínica entre melanoma inicial e tumores benignos pode ser difícil em algumas ocasiões, especialmente na ceratose seborreica pigmentada. A dermatoscopia pode ajudar; porém, os achados nem sempre são conclusivos, de modo que a histopatologia pode ser necessária para o diagnóstico correto. Descrevemos uma lesão melanocítica com aspectos clínicos e dermatoscópicos duvidosos. Nesse caso, a biópsia incisional de área suspeita, guiada pela dermatoscopia, estabeleceu o diagnóstico.